Berberine inhibitory action against zika and dengue viruses in cell cultures - Giannone, Denise Anabella (2023)
Berberine (BBR) is a plant derived isoquinoline alkaloid that displays a greatvariety of biological activities. In this study we showed that BBR exhibits astrong antiviral activity with broad spectrum of inhibition against differentstrains of Zika virus (ZIKV) and the four serotypes of dengue virus (DENV) inVero cells. The inhibitory effect of BBR on ZIKV and DENV-2 growth wasalso demonstrated in human cell lines. The analysis of BBR mode of actionshowed that the compound did not affect early events of viralmultiplication cycle or viral protein expression. By contrast, BBRstrongly impaired the formation of intracellular and extracellularinfectious viral particles. Furthermore, BBR was able to inhibit ZIKVinduced activation of ERK1/2 and p38 cell signaling pathways and alsoreduced p38 phosphorylation in uninfected cells. Like BBR, thep38 inhibitor SB202190 reduced p38 phosphorylation in bothuninfected and ZIKV infected cultures and caused a significantdiminishment of viral yields even when it was added late during theinfection. These results suggest for the first time that the inhibitoryeffect of BBR on p38 signaling might contribute to the antiviral action ofthe compound against flaviviruses.